Tropical diseases and anaesthesia. Issue 8 (August 2022) - Howell, Victoria; Bashford, Tom
Abstract: The range of infectious diseases encountered whilst working in resource-limited settings varies enormously depending on where in the world one is working, although the majority of low- and middle-income countries lie within the tropics. Human immunodeficiency virus (HIV), tuberculosis (TB) and malaria are commonly encountered when working in tropical countries and may have an impact upon anaesthesia, either as a direct result of the condition, or due to interaction with the drugs used in its management. Other infections, such as dengue, are less likely to be encountered in a patient undergoing anaesthesia but may be seen in patients in a high-dependency or intensive-care unit. Furthermore, the chronic effects of some of these diseases may impact upon anaesthesia or have complications that require surgery. It is essential therefore that the anaesthetist working within these populations has an appreciation of the tropical diseases that are endemic, set against the wider backdrop of a resource-limited population where malnutrition, poorly managed non-communicable disease and trauma may all complicate the clinical picture.